Clinical features of Sjögren's syndrome patients with autoantibodies against interferons. Issue 1 (3rd January 2019) - Burbelo, Peter D.; Browne, Sarah; Holland, Steve M.; Iadarola, Michael J.; Alevizos, Ilias
Abstract: Background: Sjögren's syndrome (SS) is an autoimmune disease characterized by immune attack on the salivary and lacrimal glands. Given the known cytokine activation and type I interferon gene expression signature found in SS, we hypothesized that anticytokine autoantibodies might be detectable by Luciferase immunoprecipitation systems in some SS patients and correlate with clinical symptoms. Results: Luciferase immunoprecipitation systems was used to screen for serum anti‐cytokine autoantibodies in 57 primary SS patients and 25 healthy volunteers. Autoantibodies were detected against GMCSF, interferon‐γ, ‐α and, ‐ω in one, two, two and six patients with SS, respectively. None of the healthy volunteers showed anticytokine autoantibodies and none of the SS or control subjects showed autoantibodies against interferon‐λ. One 51‐year old female SS subject with the highest anti‐interferon‐α and ‐ω autoantibody levels had stable autoantibody levels over the course of a year. In vitro functional testing of serum autoantibodies from this subject demonstrated partially neutralizing activity for interferon‐α signaling. Clinical information on this individual revealed a low focus score and high levels of unstimulated salivary flow, suggesting the possibility that interferon‐α autoantibody neutralizing activity may have contributed to the milder sicca symptoms. Conclusion: Overall, these findings demonstrate that a subset of SS patients (16%) harbor autoantibodies against GMCSF, interferon‐γ, interferon‐ω, and interferon‐α. These data support the observation that high levels of interferon‐α autoantibodies may attenuate disease symptoms in SS.